Common Carotid Artery Volume Flow: A Comparison Study between Ultrasound Vector Flow Imaging and Phase Contrast Magnetic Resonance Imaging - Andreas Hjelm Brandt; Jacob Bjerring Olesen; Ramin Moshavegh; Jørgen Arendt Jensen; Michael Bachmann Nielsen; Kristoffer Lindskov Hansen (MDPI AG, 2021)
Volume flow estimation in the common carotid artery (CCA) can assess the absolute hemodynamic effect of a carotid stenosis. The aim of this study was to compare a commercial vector flow imaging (VFI) setup against the reference method magnetic resonance phase contrast angiography (MRA) for volume flow estimation in the CCA. Ten healthy volunteers were scanned with VFI and MRA over the CCA. VFI had an improved precision of 19.2% compared to MRA of 31.9% (p = 0.061). VFI estimated significantly lower volume flow than MRA (mean difference: 63.2 mL/min, p = 0.017), whilst the correlation between VFI and MRA was strong (R2 = 0.81, p < 0.0001). A Bland-Altman plot indicated a systematic bias. After bias correction, the percentage error was reduced from 41.0% to 25.2%. This study indicated that a VFI setup for volume flow estimation is precise and strongly correlated to MRA volume flow estimation, and after correcting for the systematic bias, VFI and MRA become interchangeable.